Simulasi Peredam Getaran TDVA dan DDVA Tersusun Seri terhadap Respon Getaran Translasi Sistem Utama - Aini Lostari (President University, 2017)
A system can be subjected to excessive vibration if the force acting on it approaches the natural frequency of the system. The way to do it, especially for single operating frequency, is adding the dynamic vibration absorber. Generally, the dynamic vibration absorber is a mass-spring-damper addition to the main system. This study researches the effects comparison of Without Dynamic Vibration Absorber and Series Double Dynamic Vibration Absorber on the main system response. Electric motor with unbalanced masses is used as the exciter and placed on the two beams. The main mass is supported by these beams. This system has the specified dynamic equations. The main system response absorber TDVA addition gives 0.008291meter displacement rms at 1, 002 frequency-ratio. The one with DDVA system response absorber with Ma1=1/20 and Ma2 =1/20, Ma1=2/30 and Ma2 =1/30, and Ma1=1/40 and Ma2 =1/40 gives 0.001484 meter, 0.002691 meter, and 0.001343 meter. The system with SDVA gives better response than DDVA. The first absorber mass ability to reduce main mass response is disturbed by the second absorber mass existence.